Breeding Habitat Preference of the Dengue Vector Mosquitoes Aedes aegypti and Aedes albopictus from Urban, Semiurban, and Rural Areas in Kurunegala District, Sri Lanka - J. M. Manel K. Herath; W. A. Priyanka P. De Silva; Thilini C. Weeraratne; S. H. P. Parakrama Karunaratne (Journal of Tropical Medicine)
Elimination of vector mosquito larvae and their breeding environments is an effective strategy in dengue disease control. Present study examined larval density and water quality in breeding habitats and container preference of dengue vectors Ae. aegypti and Ae. albopictus. Larval surveys were conducted monthly in urban, semiurban, and rural sites in Kurunegala, Sri Lanka, from January 2019 to December 2021. Larval densities were recorded under the following three categories: type of container (16 types), type of material (6 types), and location (indoor/outdoor). Breeding preference ratios (BPRs) were calculated using Index of Available Containers and the Index of Contribution to Breeding Sites. Out of 19,234 wet containers examined, larval stages were found in 1,043 habitats. Ae. albopictus larvae were in all three areas whereas Ae. aegypti larvae were restricted to urban areas. Highest number of wet containers and highest positivity were reported from urban followed by semiurban. In general, discarded nondegradable items were the most frequent and mostly positive breeding sites. For Ae. aegypti, the most preferred breeding sites were gutters and concrete slabs. Ae. albopictus mostly preferred concrete slabs in urban areas and tyres in semiurban and rural areas. Material types such as rubber and concrete were mostly preferred by Ae. aegypti whereas ceramic was preferred by Ae. albopictus. Although plastic was the most available material type in all study sites, preference to plastic was low except for urban Ae. albopictus. Both species preferred urban indoor breeding habitats although outdoor breeding was preferred by Ae. albopictus in rural areas. Larval densities of Ae. aegypti and semiurban Ae. albopictus significantly correlated with the BPR of the container type and material type. Dengue vector larvae were found in a 6.7–9.4 pH range. Total dissolved solids and alkalinity positively correlated with preference. Information generated can be successfully used in waste management and public education for effective vector control.